2008
DOI: 10.3748/wjg.14.2434
|View full text |Cite
|
Sign up to set email alerts
|

Impact of postoperative omega-3 fatty acid-supplemented parenteral nutrition on clinical outcomes and immunomodulations in colorectal cancer patients

Abstract: AIM:To investigate the effect of omega-3 fatty acid parenteral supplementation postoperatively on clinical outcomes and immunomodulation in colorectal cancer patients. METHODS:Forty-two patients undergoing radical colorectal cancer resection with an indication for total parenteral nutrition postoperatively were enrolled in this prospective, double-blind, randomized, controlled study. Patients received total parenteral nutrition supplemented with either soybean oil (LCT; Intralipid CONCLUSION:Postoperative sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
145
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(149 citation statements)
references
References 31 publications
2
145
0
2
Order By: Relevance
“…The review goes on to describe and interpret studies using parenteral or enteral fish oil in various patient groups with a focus on immune, inflammatory and clinical outcomes. The material described is largely based upon that presented in previous review articles of this subject (1)(2)(3) , but here this information is updated with respect to additional studies of relevance (4) , new meta-analyses (5) and newly published guidelines for parenteral nutrition (6,7) .…”
mentioning
confidence: 99%
“…The review goes on to describe and interpret studies using parenteral or enteral fish oil in various patient groups with a focus on immune, inflammatory and clinical outcomes. The material described is largely based upon that presented in previous review articles of this subject (1)(2)(3) , but here this information is updated with respect to additional studies of relevance (4) , new meta-analyses (5) and newly published guidelines for parenteral nutrition (6,7) .…”
mentioning
confidence: 99%
“…Similar diets have been shown to influence colorectal carcinogenesis [23][24][25] . The present study tested the ability of a hyperlipidic and hypercaloric diet to inhibit the development of ACF in the colonic mucosa of rats treated with AOM.…”
Section: Discussionmentioning
confidence: 99%
“…Figure 1 shows the process for identifying potentially eligible studies and exclusion criteria. After elaborative screening, 34 articles were assessed by full text and 17 studies with 753 patients [2,[10][11][12]15,16,[23][24][25][26][27][28][29][30][31][32][33] were included for the review. However, three publications [2,24,30,31,33] are same study that reported different outcomes.…”
Section: Selection and Characteristics Of Studiesmentioning
confidence: 99%
“…Nine studies reported the occurrence of infectious postoperative complications [11,12,23,26,27,[29][30][31][32]. The incidence of infection was 8.8% in the intervention group (24/273) and 20.1% in the control group (56/271).…”
Section: Clinical Outcomesmentioning
confidence: 99%
See 1 more Smart Citation